SOCIAL WELL-BEING, PSYCHOLOGICAL WELL-BEING DAN EMOTIONAL WELL-BEING: STUDI KAUSAL KOMPARATIF PADA PRAKTISI SENI BELA DIRI BIMA DAN KEBUGARAN FISIK - Budiarto, Yohanes (Jurnal Psikologi : Media Ilmiah Psikologi, 2018)
AbstactIndividual health promotion includes preventative and curative measures. In the holistic model of public health, the promotion of mental health is an effort that complements the bio-medical approach. Various activities can affect the promotion of mental health is to exercise regularly physical exercise or actively involved in martial arts activities. The positive impacts of joining health clubs as well as martial arts groups to mental health such as increased self-esteem, self-confidence, and subjective well-being have been summarized by many researchers. However, inconsistent results regarding the impact of following the martial arts against the psychological condition of individuals are also found. Some researchers have found that involvement in martial arts increases anti-social attitudes and involvement in violent acts. This study attempts to reveal the phenomenon by conducting a comparative causal study ex post facto on health-care participants in health clubs and BIMA martial arts participants. From the research results obtained the findings that participants BIMA martial arts and sports participants in health clubs have emotional, psychological and social well-being is high. However, only the social well-being participants of the BIMA martial art (M = 4,969, SD = .691) were higher than the club's fitness participants (M = 4.55 3, SD = 1.054); t (58), p = .009. Keywords: martial arts, psychological well-being, emotional well-being, social well-being. AbstrakPromosi kesehatan yang dilakukan individu meliputi upaya-upaya preventif dan juga kuratif. Dalam model holistik kesehatan publik, promosi kesehatan mental merupakan upaya yang melengkapi pendekatan bio-medis. Berbagai kegiatan yang dapat berpengaruh terhadap promosi kesehatan mental adalah dengan melakukan kegiatan olah raga fisik secara teratur atau terlibat aktif dalam kegiatan seni bela diri. Berbagai dampak positif dari mengikuti klub kesehatan dan juga kelompk seni bela diri terhadap kesehatan mental seperti meningkatnya self-esteem, kepercayaan diri, hingga kesejahteraan subyektif telah dirangkum oleh banyak peneliti. Namun demikian hasil yang inkonsisten terkait dampak mengikuti seni bela diri terhadap kondisi psikologis individu juga ditemukan. Beberapa peneliti menemukan bahwa keterlibatan dalam seni bela diri meningkatkan sikap anti sosial dan keterlibatan dalam tindakan kekerasan. Penelitian ini berusaha mengungkapkan fenomena tersebut dengan melakukan studi kausal komparatif secara ex post facto terhadap peserta olah raga kesehatan di klub kesehatan dan peserta seni bela diri BIMA. Dari hasil penelitan diperoleh temuan bahwa peserta seni bela diri BIMA dan peserta olah raga di klub kesehatan memiliki emotional, psychological dan social well-being yang tinggi. Namun demikian, hanya social well-being peserta seni bela diri BIMA (M=4.969, SD =.691) yang lebih tinggi daripada peserta klub kebugaran (M = 4.55 3, SD =1.054); t (58), p =.009. Kata kunci: seni bela diri,  psychological well-being, emotional well-being, social well-being.